Intestinal schistosomiasis in Uganda at high altitude (>1400 m): malacological and epidemiological surveys on Mount Elgon and in Fort Portal crater lakes reveal extra preventive chemotherapy needs. Issue 1 (December 2017) - Stanton, Michelle; Adriko, Moses; Arinaitwe, Moses; Howell, Alison; Davies, Juliet; Allison, Gillian; LaCourse, E.; Muheki, Edridah; Kabatereine, Narcis; Stothard, J.
Abstract Background Intestinal schistosomiasis is of public health importance in Uganda but communities living above 1400 m are not targeted for control as natural transmission is thought unlikely. To assess altitudinal boundaries and at-risk populations, conjoint malacological and epidemiological surveys were undertaken on Mount Elgon (1139 m–3937 m), in Fort Portal crater lakes and in the Rwenzori Mountains (1123 m–4050 m). Methods Seventy freshwater habitats [Mount Elgon (37), Fort Portal crater lakes (23), Rwenzori Mountains (8) and Lake Albert (2)] were inspected forBiomphalaria species. Water temperature, pH and conductivity were recorded. A parasitological examination of 756 schoolchildren [Mount Elgon (300), Fort Portal crater lakes (456)] by faecal microscopy of duplicate Kato-Katz smears from two consecutive stool samples was bolstered by antigen (urine-CCA dipstick) and antibody (SEA-ELISA) diagnostic assays. Results Biomphalaria spp. was found up to 1951 m on Mount Elgon and 1567 m in the Fort Portal crater lakes. Although no snail from Mount Elgon shed cercariae, molecular analysis judged 7.1% of snails sampled at altitudes above 1400 m as having DNA ofSchistosoma mansoni ; in Fort Portal crater lakes three snails shed schistosome cercariae. Prevalence of intestinal schistosomiasis as measured in schoolchildren by Kato-Katz (Mount Elgon = 5.3% v. Fort Portal crater lakes = 10.7%), CCA urine-dipsticks (18.3% v. 34.4%) and SEA-ELISA (42.3% v. 63.7%) showed negative associations with increasing altitude with some evidence of infection up to 2000 m. Conclusions Contrary to expectations, these surveys clearly show that natural transmission of intestinal schistosomiasis occurs above 1400 m, possibly extending up to 2000 m. Using spatial epidemiological predictions, this now places some extra six million people at-risk, denoting an expansion of preventive chemotherapy needs in Uganda.